2008
DOI: 10.1016/j.abb.2008.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complex of glutathione S-transferase pi and 1-cysteine peroxiredoxin

Abstract: Glutathione S-transferase pi has been shown to reactivate 1-cysteine peroxiredoxin (1-Cys Prx) by formation of a complex. A model of the complex was proposed based on the crystal structures of the two enzymes. We have now characterized the complex of GST pi/1-Cys Prx by determining the M w of the complex, by measuring the catalytic activity of the GST pi monomer, and by identifying the interaction sites between GST pi and 1-Cys Prx. The M w of the purified GST pi/1-Cys Prx complex is 50,200 at pH 8.0 in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 32 publications
1
59
0
2
Order By: Relevance
“…This involves heterodimerization with GSH transferase (GST), followed by GSH-mediated reduction and enzyme reactivation (27). GST is thought to serve as a source of activated GSH catalyzing glutathionylation of the oxidized peroxidatic cysteine residue, and GSH is the reductant in this mechanism which regenerates the active 1-Cys peroxiredoxin (28,40). More recently, ascorbate has been proposed to function as a reductant for 1-Cys peroxiredoxins from diverse species (31).…”
Section: Discussionmentioning
confidence: 99%
“…This involves heterodimerization with GSH transferase (GST), followed by GSH-mediated reduction and enzyme reactivation (27). GST is thought to serve as a source of activated GSH catalyzing glutathionylation of the oxidized peroxidatic cysteine residue, and GSH is the reductant in this mechanism which regenerates the active 1-Cys peroxiredoxin (28,40). More recently, ascorbate has been proposed to function as a reductant for 1-Cys peroxiredoxins from diverse species (31).…”
Section: Discussionmentioning
confidence: 99%
“…GSTpi was shown to form a complex with the inactive form of 1-CysPrx (both in vivo and in vitro), which accounts for reactivation of 1-Cys-Prx. 4,13 Mitogen-activated protein kinases (MAPKs) are eukaryotic enzymes at the core of the MAPK cascade. They transduce signals sent by cell surface receptors to important intracellular targets (both cytosolic and nuclear), controlling cell proliferation, differentiation, inflammation, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Chaotropic salts have been used to disrupt electrostatic interactions in proteins by shielding charges between subunits (20 -22). Studies conducted in our laboratory showed that the molecular mass of GST is decreased by the addition of potassium bromide, implying that electrostatic interactions are important forces holding the subunits together (23).…”
mentioning
confidence: 99%